Denmark and Russia: What can we learn from the historical comparison of two great Arctic agricultural empires? - Korchmina, Elena S.; Sharp, Paul (Russian Journal of Economics, 2024)
We propose that the "historically relevant" comparison of the Danish and Russian Empires from the early eighteenth century until the First World War presents a useful starting point for a promising research agenda. We justify the comparison by noting that the two empires enjoyed striking geographical, political and institutional similarities. Beyond this, we also demonstrate that the two empires were bound together by war, royal marriage, and migration. We suggest some examples of what might be investigated, with a particular focus on agriculture, due to its importance to both Danish and Russian economic history. Finally, we zoom in on the role Danish experts played for developing the Russian butter industry.